Distribution of dermatitis of the parasitic origins at sheep in farms of the North Caucasus - B. M. Bagamayev (Российский паразитологический журнал)
Distribution and extent of manifestation of diseases of an integument in dif-ferent climatic zones of North Caucasus region in 2001–2010 is studied. Dermatitis of parasitic etiology noted at 88–91 % of sheep in different zones of the region. The maximum contamination of sheep by ectoparasites was in droughty zone. Dermatitis of noncontagious and infectious etiology is established respectively at 5–6 and 4–5 % of sheep. In 2001–2010 the frequency of disease of skin of parasitic etiology significantly didn't change. Most sheep were struck with Psoroptes ovis and insects of Melophagus ovinus. 47 % of sheep are infected with ectoparasites. Damages of skin noted at sheep during all seasons. In the first half of winter the number of sick sheep raised, especially at the dense contents. Among young growth skin disease extend quicker. Preventive treatment of sheep cover 20–50 % of livestock and they are carried out within the year. 45 % of processings of sheep carry out in winter.